Teachers' Efforts in Improving Students' Reading the Qur’an - Wulandari, Viona Dwi; Putri, Cyntia Tiara; Ramadhany, Nur Fadilah; Iskandar, M. Yakub (International Journal of Multidisciplinary Research of Higher Education, 2022)
This study aims to explore the teacher’s effort to upgrade students' the Qur’an recitation. The study used a qualitative method with a phenomenology approach, research data is taken through direct interviews with three informants (Islamic education teachers) with deep interviews. All interviews were then analyzed thematically using NVivo 12 software. Overall, the results of the analysis showed that there were six efforts the teacher used to upgrade students’ the Qur’an recitation. The six efforts are: i) explain the subject, ii) know the makharijul huruf, iii) explain the tajwid, iv) create the groups, v) the present illustration and video, vi) remind and guide. The results of this study can be used as initial data for future researchers in examining different issues.